“Obtención y caracterización del almidón de jergón sacha (dracontium loretense)” - Ramírez Velásquez, Mary De Jesús (2004)
The present research work was carried out in laboratories of Análysis and composition of agroimdustry products ( ANACOMPA), nom - food agroimdustry products technology (TEPANAL), and engineering and desing of agroindustrial engineering faculty at San Martin National University - Peru. Research seeks to incentive the use of wild cultivations not even utilized, as is case of Jergon Sacha ( Dracontium Joretense ) , which arew dispersed in all amazonia, im form cultivated and wild, being used chiefly far the cure of various diseases. The study comprehended severa! analyses, both raw material and finished product as well as chemical and necessary sensory analyses. Samples of Jergon Sacha ( Dracontium loretense) snackie were collected in the town of pamashto, located 1 O km from province Lamas - San Martin, zone at temperatures minimum 17ºC and maximum 20ºC, situated with an altitude 800meters on sea level (M.O.S.L). lt reapped the snackies taking into account their size that was from 15 to 25 cm. Snackie presented light cream color and circular flattened form, with average diameter 16.8 cm and average thickness 7.13 cm, average density of them was 1.064 g/cm3 , chemical determination of them gave a proximate composition with moisture 75.20%, protein 0.80%, carbohydrate 22.40%, fat 0.20%, fibre 0.13% and ash 1.10%. Processing flow far obtainment of Jergon Sacha ( Dracontium loretense) snackied was the following: Raw material Washed Peeled Cut off Liquefied Sifted Settled Dried Sifted Packed. To determine best dried conditions of final products, made a semsory evaluation with five - point hedonic scale; through which evaluated color, texture and general appearance characteristics. Results indicated that best treatment was 50°C with constant air velocity 2m/s. Finished ( starch) product proximate composition was: moisture 10.9%, protein 0.22%, fibre 0.05%, ash 0.45%, fat 0.13%, carbohydrate 88.25%. The pH was 4.53 and acidity gave 0.048% expressed as sulphuric acid. Starch particles passed by mesh 200, with a hole of 75 um. The gelatinization temperature initiated at 70°C, being higher point at 95ºC. Maximum viscosity obtained at 95°C, for three experimental temperatures being 930 cp at SOºC, 1000 cp at 55ºC and 1040 cp at 60°C, respectively. The amilose rate calculated of starch was 26.30 % at 625 mm. In chelating test , obtained a good firm and transparent starch paste. Starch color was compared with a Ridgway colors identification table, which idenUfied an ocher yellow color that pointed on 68% color and 32% neutral grey. This color of 68% contains 65% orange and 35% yellow. The yield of the tarch was of 15.53%,